Synthesis and Characterization of Tissue-engineered Collagen Hydrogels for the Delivery of Therapeutic Cells - McEwan, Kimberly A. (Université d'Ottawa / University of Ottawa, 2013)
The expanding field of tissue engineering provides a new approach to regenerative medicine for common ailments such as cardiovascular disease and type-I diabetes. Biomaterials can be administered as a delivery vehicle to introduce therapeutic cells to sites of damaged or diseased tissue. A specific class of biomaterials, termed hydrogels, is suitable for this application as they can provide a biocompatible, biodegradable scaffold that mimics the physical properties of the native soft tissue. Injectable hydrogels are increasingly being developed for biomedical applications due to their ability to be delivered in a minimally invasive manner. One potential use for such materials is in the delivery of therapeutics such as cells or growth factor-releasing particles. In this study, the first aim was to determine the interactive effects between collagen-based hydrogels and additives (cells and microspheres) for cardiac regeneration. The results demonstrated that the addition of either cells or microspheres to a collagen-based hydrogel decreased its gelation time and increased its viscosity. Increased cross-linker concentrations resulted in lower cell viability. However, this cell loss could be minimized by delivering cells with the cross-linker neutralizing agent, glycine. As a potential application of these materials, the second aim of this study was to develop a hydrogel for use as an ectopic islet transplant site. Specifically, collagen-chitosan hydrogels were synthesized and characterized, with and without laminin, and tested for their ability to support angiogenic and islet cell survival and function. Matrices synthesized with lower chitosan content (20:1 collagen:chitosan) displayed greater cell compatibility for both angiogenic cells and for islets and weaker mechanical properties, while matrices with higher chitosan content (10:1 collagen:chitosan) had the opposite effect. Laminin did not affect the physical properties of the matrices, but did improve angiogenic cell and islet survival and function. Overall the proposed collagen-based hydrogels can be tailored to meet the physical property requirements for cardiac and islet tissue engineering applications and demonstrated promising cell support capabilities.
Keywords: biomaterials; collagen hydrogels; type-I diabetes; cardiovascular disease; islet cells; angiogenic cells